SEMANGAT KERJA GURU DI SMK NEGERI KABUPATEN SOLOK SELATAN - Febri Yanti (Universitas Negeri Padang, 2013)
The purpose of this study was to know about teacher the employee morale in SMK Negeri Kabupaten Solok Selatan. The population are 127 employees and samples 31 employees. Sampel the taken is 25% from amount of population amounting 31 people, who were taken using propotional random sampling technique. This quisionare has been tested the validity and the reliability using SPSS program. Data were analyzed using mean score formula. In General teacher the employee morale in SMK Negeri Kabupaten Solok Selatan at high category enough with mean score as a whole is 3,56. the employee morale teacher in SMK Negeri Kabupaten Solok Selatan can be told high enough evaluated from enthusiastic aspect, creativity, participation and cooperation. Keyword: Semangat kerja